Sport psychology service provision: Preferences for consultant characteristics and mode of delivery among elite Malaysian athletes - Ponnusamy, V.; Grove, J. R. (Journal of Sports Science & Medicine, 2014)
Factors relevant to the working alliance between athletes and sport psychology consultants were investigated in a sample of elite Malaysian athletes (n = 217). The athletes represented a variety of team and individual sports, and they provided information about the perceived importance of seven consultant characteristics/behaviors as well as seven program delivery options. At a full-sample level, general preferences were expressed for consultants to lead a physically active lifestyle, regularly attend training sessions and competitions, and have prior experience as an athlete or coach. General preferences were also expressed for program content to be determined by the coach or consultant, and for regular, small doses of mental skills training to be delivered in a face-to-face context throughout the year. At a sub-group level, team sport athletes had stronger preferences than individual sport athletes for program delivery on a group/team basis, while individual sport athletes had stronger preferences than team sport athletes for having a role in determining program content. Findings are discussed in relation to dominant value themes within Malaysian society and the reinforcement of these themes within specific sport subcultures.